Amphiphilic derivatives of (3β,17β)-3-hydroxyandrost-5-ene-17-carboxylic acid - Özdemir, Zülal; Bildziukevich, Uladzimir; Šaman, David; Havlíček, Libor; Rárová, Lucie; Navrátilová, Lucie; Wimmer, Zdeněk (Steroids, 2017)
A series of amphiphilic derivatives of (3β,17β)-3-hydroxyandrost-5-ene-17-carboxylic acid (1) with the polyamine spermine and three other diamines, 1,2-diaminoethane, piperazine and cadaverine, were synthesized and their antimicrobial activity and cytotoxicity were investigated. Among the target compounds, several ones showed antimicrobial activity on Gram positive and Gram negative microorganisms. The most active compounds were 20 (Streptococcus mutans CCM 7409, 3.125 µM), 16 (Streptococcus mutans CCM 7409, 12.5 µM) and 10d (Escherichia coli CCM 3954, 12.5 µM). In addition, compounds 5d, 10d, 13 and 20 displayed cytotoxicity on CEM (12.1 ± 2.1 µM, 7.6 ± 1.0 µM, 19.0 ± 0.4 µM and 5.9 ± 0.7 µM, respectively). Two additional compounds displayed medium cytotoxicity on CEM, 5a (34.6 ± 5.2 µM) and 5c (37.7 ± 5.9 µM). The compound 13 and 20 displayed high toxicity also on normal fibroblasts.
Keywords: Androstenes; Polyamine; Antimicrobial activity; Microbial Sensitivity Tests; Cytotoxicity; androsteny; kyseliny karboxylové; Carboxylic Acids; mikrobiální testy citlivosti; antibakteriální látky; Anti-Bacterial Agents; Amphiphile; Diamine; Escherichia coli; Steroid; polyaminy; Polyamines